EFISIENSI SALURAN PEMASARAN JAGUNG MANIS DI DESA RASAU JAYA I KECAMATAN RASAU JAYA KABUPATEN KUBU RAYA - HERIANTO, HERIANTO; MUANI, ANI; DOLOROSA, EVA (Jurnal Social Economic of Agriculture, 2015)
This study aims to : 1) Determine the functions of marketing channels. 2) Determine the value of the cost advantage is issued by each each of maize marketing channels that exist in the study area. 3 ) Know efficiency of the marketing channels of corn. This study used a survey method that is done by taking a sample of the population and the questionnaire as a data collection tool that subject , and immediately went to study sites to obtain information necessary research.  The most efficient channel is the channel the consumer to the producer